A matrix-based conversion of Robustness Diagrams with Loop and Time Controls to Petri Nets with abstract arcs handling - Flores, Angelo Louis A.
Robustness Diagrams with Loop and Time Controls (RDLTS) effectively model complex workflows but converting them to Petri Nets (PNs) for automated, matrix-based analysis is challenging, particularly when handling Reset-Bound Subsystems (RBS) and multiple abstract arcs. This research presents a formal, matrix-based algorithm to directly convert the matrix representation of an RDLT into the corresponding matrices and initial marking of an equivalent Reset Workflow Net (RWF-Net). The algorithm systematically processes RDLT structural and attribute matrices using matrix operations to determine the necessary PN components and connections. It specifically addresses the mapping of the two cases for handling SPLIT points and provides a method for handling multiple parallel abstract arcs. The preservation of Weak and Easy Soundness properties during this matrix-based conversion is also investigated.